O limite constitutivo entre o cogito cartesiano e o sujeito da psicanálise construído no texto A Ciência e a verdade - Magalhães, Natalia Mendonça (2015)
The following thesis is the result of a research that claims the psychoanalysis theory on the subject of science. According to Jacques Lacan, the origin of Psychoanalysis is based on modern science which speech establishes its real meaning. That is the point we were chasing through this papers. Therefore, the works of Lacan and other lacanian thinkers after him says that Psychoanalysis is able to stand up by itself even its based upon modern science in the beginning. The concept of subject of science that Lacan started up in his text The Science and the Truth (1965) come from his understanding of René Descartes works much before him. The concept of human being and the modern subject as Lacan could realize in the Descartes´ Meditation is founded on how this opus notice reason and doubt. We approach the theme through the analysis of the six meditations, beginning with the thinking subject. This present dissertation aims to follow the knowledge of Philosophy that supports lacanian psychoanalysis theory and its modern foundations.